A comprehensive review of hydrodynamic mechanisms and heat transfer characteristics for microencapsulated phase change slurry (MPCS) in circular tube. (October 2019) - Yang, Liu; Liu, Shuli; Zheng, Hongfei
Abstract: Microencapsulated phase change slurry (MPCS) shows remarkable merits especially in narrow temperature range and high energy density for the thermal energy application. It combines the advantages of the carrier fluid and the phase change materials. However, the performance of slurry is limited by the poor thermal conductivity and pumping energy of microcapsules. This paper reviews the extensive research findings of the rheological behaviours, the hydrodynamic properties, the heat transfer characteristics and the heat transfer enhancement for MPCS. The aims are to remark the research progresses about the flow and heat transfer performance, as well as to promote further study in this field. The paper presents the basic thermophysical parameters for MPCS, such as phase change temperature, specific heat capacity, thermal conductivity and sub-cooling. Then, the state of the art in rheological behaviours and hydrodynamic properties for MPCS are analysed. The present work compares the existing literatures towards to the forced convective heat transfer characteristics achieved through experimental and numerical investigations. Furthermore, the melting/solidifying process, the enhancement mechanisms of heat transfer and a plenty of enhanced techniques are elaborated. This paper also reports several representative applications of MPCS in recent years. It is expected that this work can give interesting and valuable insights on the hydrodynamic mechanisms and heat transfer characteristics of MPCS, and promote the further studies in strengthening the comprehensive performance of MPCS. Highlights: The rheological behaviours and hydrodynamic properties of MPCS have been analysed. The forced convective heat transfer characteristics and the comprehensive performance of MPCS have been discussed. The enhancement mechanisms of heat transfer for MPCS and enhanced techniques are elaborated. The applications of MPCS are also remarked.